2007
DOI: 10.1007/s00439-006-0310-2
|View full text |Cite
|
Sign up to set email alerts
|

Segregation analysis of 1,546 prostate cancer families in Finland shows recessive inheritance

Abstract: Prostate cancer (PCa) is the most frequently diagnosed cancer in men worldwide. As PCa is a complex, multigenic disease, it has been challenging to establish its genetic basis, with strong risk factors obscured by the genetically heterogeneous patient populations often available for analysis. Worldwide the PCa phenotype has been further complicated based on the frequent inclusion of cases in which prostate specific antigen (PSA)-tests allow early diagnosis of possibly latent disease. Thus, previous segregation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…Recently, Christensen et al (16) showed that a subset of Utah high-risk pedigrees with a familial history of prostate cancer showed nominal linkage evidence on chromosome 8q (heterogeneity LOD score, 1.67). Our results, which included a familial prostate cancer history but was not restricted to a high-penetrance model to a major gene (Carter's criteria), could be compatible with our previous observation of a brother-brother dependence inheritance (17) and the (18).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, Christensen et al (16) showed that a subset of Utah high-risk pedigrees with a familial history of prostate cancer showed nominal linkage evidence on chromosome 8q (heterogeneity LOD score, 1.67). Our results, which included a familial prostate cancer history but was not restricted to a high-penetrance model to a major gene (Carter's criteria), could be compatible with our previous observation of a brother-brother dependence inheritance (17) and the (18).…”
Section: Discussionsupporting
confidence: 91%
“…This difference in risk has been found by other studies [Monroe et al, 1995;Narod et al, 1995;Woolf, 1960]. Some evidence for a recessive component was also reported in a previous publication using a subset of the Australian data [Cui et al, 2001], and more recently of Finnish prostate cancer families [Pakkanen et al, 2007].…”
Section: Discussionsupporting
confidence: 53%
“…The best-fitting model was a simple multifactorial non-genetic model. The recent study conducted in Finland also found a significant paternal regressive coefficient that is indicative of a polygenic component [Pakkanen et al, 2007]. There are several possible explanations for the differences in findings between these analyses.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Although the studies are in diverse populations, seven analyses report evidence for a single major gene with a rare autosomal dominant eVect, especially in families with early ages of onset (Carter et al 1992;Conlon et al 2003;Cui et al 2001;Gronberg et al 1997;Schaid et al 1998;Valeri et al 2003;Verhage et al 2001). Two studies provide evidence for recessive inheritance (Cui et al 2001;Pakkanen et al 2007), while Gong et al (2002) suggest that a multifactorial model best Wts the available data.…”
Section: Introductionmentioning
confidence: 95%